Induction of colitis in mice (T-cell transfer model) - Weigmann, Benno (Methods in Molecular Biology, 2014)
Animal model of intestinal inflammation is essential for the understanding of the pathomechanisms of inflammatory bowel diseases like Crohn's disease and ulcerative colitis. Typically, naïve T-cells were transferred into immunocompromised mice and develop gut inflammation because of inappropriate downregulation. Here, we describe the isolation, purification, and transfer of CD4(+)CD25(-) T-cells into recipients to obtain an experimental colitis model for the analysis of pathogenesis.
EVALuna2:1909